Edukasi dan Pendampingan melalui Coaching untuk Meningkatkan Pemahaman dan Keterampilan RedSeller New Joiner - Diana Amelia; Ika Korika Swasti (ManBiz: Journal of Management and Business, 2026)
Digital platform-based partnership models are growing in line with the increasing demand for flexible work and community economic participation. The RedSeller program is one of RedDoorz's official digital partnerships that allows individuals from diverse backgrounds to become marketing partners for accommodation services. However, when they first join, new RedSellers often face obstacles such as a limited understanding of the work system, use of the application, and effective marketing strategies. This situation results in low readiness and confidence among partners in carrying out promotional activities. This activity aims to improve the understanding of new RedSellers through coaching-based education and mentoring. The methods used include intensive online coaching, presentation of material on the RedSeller work system, use of the RedSeller application, and mentoring on promotional strategies through multi-platform social media. The evaluation was conducted descriptively and qualitatively by observing changes in partners' understanding, actions, and readiness before and after coaching. The results of the activity showed an increase in partners' understanding of the role of RedSeller, operational flow, and application usage, followed by increased confidence in conducting promotions and the ability to apply marketing communication strategies in a more focused manner. These findings confirm that the coaching approach is relevant as an educational strategy and initial guidance in supporting the readiness of new partners in the partnership-based digital marketing ecosystem.